DEEP STRUCTURE MODELING OF GOLOVANIVSK SUTURE ZONE ON THE BASIS OF GEOELECTRIC DATA - Burakhovych, T.; Ganiev, O.; Shyrkov, B. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The article reviews the results of the preliminary three-dimensional modeling of Golovanivsk suture zone (GSZ) of the Ukrainian shield (USh) that was made on the basis of experimental magnetotelluric sounding (MTS) and magnetovariational profiling (MVP) data. According to various scientists, this part of USh is a regional structure with low conductivity of the crust. It is characterized by a pronounced anisotropy of the subsurface resistivity and its sharp variability both in lateral direction and in depth. Deep fault zones (Talnivska, Pervomayska, Vradiyivska, Gvozdavska) limiting GSZ and its structural-formational parts stand out as high conductivity zones, both at the subsurface and at depths of 15-30 km. The processing of modern magnetotelluric observations using digital equipment on the "Pervomajskiy" profile, using software system PRC_MTMV [3] made it possible to identify the anomalous conductive parts of GSZ localized in the zones of deep faults (Talnivska, Pervomayska, Yemylivska). These results were used to construct a three-dimensional geoelectric model. The method for construction of deep conductivity models is based on their multistage sequential calculation and comparison with experimental data. At the initial stage of modeling, MVP data are used while MTS data are used at the final stage. According to the simulation results, two sublatitudinally oriented superficial zones of high conductivity were revealed in the northern part of GSZ. Submeridional conductivity anomalies were found southward, which coincide with the parts of Yemylivska, Pervomayska and Zvenigorodsko-Bratska fault zones. Model calculations allowed to reveal several types of conductivity anomalies orientation: sublatitudinal and submeridional; such anomalies correspond with subsurface and deep conductivity anomalies that were used to build the three-dimensional model. At the depths of 100-2500 m, galvanically connected objects of submeridional strike were detected. Those objects manifested themselves in the junction zone of Pervomayska, Yemylivska, Zvenigorodsko-Bratska fault zones. These anomalies are in good agreement and spatially combined with the model of the Kirovograd ore region [7]. In the depth interval of 10-15 km to 20-30 km the obtained model contains several areas of high conductivity: in the axial part of GSZ and Pervomayska fault zone; in southern part of Pervomayska fault zone; in the south of GSZ, Talnivska fault zone; sublatitudinal zone in the Pre Black Sea depression.
Keywords: suture zone; fault zone; magnetotelluric sounding; magnetovariation profiling; conductive anomaly